Photonic Nanostructures Patterned by Thermal Nanoimprint Directly into Organo‐Metal Halide Perovskites. Issue 11 (19th January 2017) - Pourdavoud, Neda; Wang, Si; Mayer, André; Hu, Ting; Chen, Yiwang; Marianovich, André; Kowalsky, Wolfgang; Heiderhoff, Ralf; Scheer, Hella‐Christin; Riedl, Thomas
Abstract : Photonic nanostructures are created in organo‐metal halide perovskites by thermal nanoimprint lithography at a temperature of 100 °C. The imprinted layers are significantly smoothened compared to the initially rough, polycrystalline layers and the impact of surface defects is substantially mitigated upon imprint. As a case study, 2D photonic crystals are shown to afford lasing with ultralow lasing thresholds at room temperature.